2015
DOI: 10.18039/ajesi.95186
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Relationship between Personality and Patterns of Facebook Usage: A Review Article

Abstract: Son yıllarda, Facebook sosyal paylaşım sitesinin kullanımı oldukça yaygınlaşmıştır. Bu gözden geçirme çalışmasında, utangaçlık, bencillik ve 5 Faktör kişilik yapısının alt faktörleri olan dışadönüklük, öz disiplin, uyumluluk, yeniliğe açıklık ve nevrotiklik kişilik özellikleri ile Facebook kullanımı arasındaki ilişkileri araştıran çalışmaların sonuçlarının bütüncül bir bakış açısı ile değerlendirilmesi amaçlanmaktadır. Araştırma kapsamında veri tabanlarında 'Facebook ve kişilik özellikleri', 'Facebook kullanıc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In addition, pride and guilt predicted SNS over shyness. These findings are consistent with the literature and supported by different studies (Chan, 2014;Laghi et al, 2013;Orr et al, 2008;Sheldon, 2013Sheldon, , 2012Ryan & Xenos, 2011;Wang et al, 2015;Yelpaze & Ceyhan, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, pride and guilt predicted SNS over shyness. These findings are consistent with the literature and supported by different studies (Chan, 2014;Laghi et al, 2013;Orr et al, 2008;Sheldon, 2013Sheldon, , 2012Ryan & Xenos, 2011;Wang et al, 2015;Yelpaze & Ceyhan, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…According to a study (Çalışkan & Özbay, 2015), individuals tend to use social media to search for an environment in which they can express themselves, feel cared for, and be respected; this is especially true when their opinions are not valued in the home environment and the level of sharing among family members is low (Amichai‐Hamburger & Ben‐Artzi, 2003; Çalışkan & Özbay, 2015). However, a study examining 40 studies on Facebook reported that individuals, who cannot establish their identities in natural social environments, try to compensate for this lack of skills with online communication, but this attempt still does not replace natural social relations (Yelpaze & Ceyhan, 2015).…”
Section: Discussionmentioning
confidence: 99%